The impact of intravenous thrombolysis on outcome of patients with acute ischemic stroke after 90 years old. Issue 1 (December 2016) - Sagnier, S.; Galli, P.; Poli, M.; Debruxelles, S.; Renou, P.; Olindo, S.; Rouanet, F.; Sibon, I.
Abstract Background Age increases the risk of mortality and poor prognosis following stroke. The benefit of intravenous thrombolysis in very old patients remains uncertain. The purpose of the study was to evaluate the efficacy and safety of thrombolysis in very old patients considering their perfusion-imaging profile. Methods We conducted a retrospective study including patients older than 90 y.o. admitted for an acute ischemic stroke. A computed tomography perfusion-imaging (CTP) was performed in patients who received thrombolysis. Primary outcome was the functional status at 3 months, assessed by the modified Rankin scale (mRS). Secondary outcomes were the rate of hemorrhagic transformations, duration of hospitalization and the rate of death in the first 7 days. Patients receiving thrombolysis were compared with an age-matched group of non-thrombolysed patients. Results 78 patients were included (31 % male, aged 92 ± 1.7 y.o). 37 patients received thrombolysis and among them, 30 had CTP with a mismatch. The three months mRS was not significantly different in the two groups (mRS 0–2: 5 % and 7 % in the thrombolysed and non-thrombolysed group, respectively). Hemorrhagic transformations were more frequent in the thrombolysed group (54 % versus 12 %, p  = 0.002) and symptomatic intracranial hemorrhage tended to be associated with mRS at three months and death in the first 7 days. Duration of hospitalization was longer in the thrombolysed group (10 days ± 12 versus 7 days ± 9, p  = 0.046). Conclusions Patients who received thrombolysis did not have a better functional prognosis than non-thrombolysed patients.